Lattice modes of solid nitrogen to 104 GPa: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Olijnyk, H.; Jephcoat, A. P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
Lattice modes of solid nitrogen were studied by Raman spectroscopy at room temperature to 104 GPa using the diamond anvil technique. Changes in the lattice mode spectral features correlate with those observed in the vibronic spectra suggesting symmetry changes of the crystal lattice. The changes in thespectral features mainly appear as branchings of existing modes supporting the view of a close structural relationship among these high pressure phases.